Pengaruh Pengangguran, Investasi Dan Produk Domestik Regional Bruto (PDRB) Terhadap Jumlah Penduduk Miskin di Provinsi Aceh - Siska Yanti; Cut Putri Sari (LPPM UNIMAL, 2023)
This study aim to know the influence the Unemployment, Investment, and Gross Regional Domestic Product (GRDP) to the Number of Poor People in 5 Districts/Cities in Aceh Province. The data used in this study is secondary time series data for the 5 year period 20172021. Methods of data analysis in this study using panel data regression analysis. The results of thestudy with a significance level of 5% show that unemployment has a positive and significant effect ion the number of poor people, investment has no significant effect ion the number of poor people and Gross regional domestic product (GRDP) has a negative and significat on the number of ipoor people in 5 districts/cities in Aceh province.